WEB INTERFACE FOR OPTIMIZATION OF FREIGHT TRANSPORTATIONS USINGMETHODS OF DECISION-MAKING IN CONDITIONS OF COMPLETE INFORMATION - DOBULIAK, LESIA; SOKHAN, IHOR; FUNDAK, LESIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Have you ever wondered how much it costs to transport a product that you see on the shelves of a store/supermarket every day? After all, any goods are transported by trucks, perhaps even not only within the borders of the country, but also abroad, and in order to be able to do this, companies use both small-sized trucks and large-sized ones to transport as many products as possible in one trip. And this is the right approach, because the fewer trips will be made, the lower will be the fuel costs embedded in any product. What if the truck carrying the goods was not completely full? Potentially, it would be possible to distribute the product in such a way as to fit as many units of the product as possible in one truck, so that the company does not incur some costs. However, this is not always easy to do. Small shops own a small number of minibuses, so they transport only the most necessary goods. However, for the "big players" this is a big problem. These are mostly supermarkets that have several branches in the city or even the country, accordingly, the goods need to be delivered not to one point, but to several. And here the question arises: how to transport goods to several points, while all the necessary goods for each branch in such a way as to reduce transportation costs. However, in addition to fuel, there are many other factors to consider, such as: the capacity of the truck, its carrying capacity, payment to drivers for their services, distance, etc. All these factors together create another problem: how to organize it all correctly so as not to get lost in unnecessary numbers, to concentrate on the main thing and to simplify this process as much as possible? The best solution will be to develop a platform that will enable organizations to manage transportation and costs in such a way as to reduce them as much as possible through the correct distribution of goods and minimizing the number of trucks. In order to reduce costs due to the correct distribution of goods on trucks, optimization algorithms NFA, FFA, WFA, BFA were applied to solve the problem of packing into containers. A proprietary SFA algorithm is also proposed, the idea of ​​which is to divide the cargo into several parts, provided that it does not fit completely into the container.